Perilaku Masyarakat Pengendara Kendaraan Bermotor Dalam Berlalu Lintas di Kota Medan - Dewantara Bangun; Fikarwin Zuska; Bengkel Ginting (Universitas Medan Area, 2022)
The purpose of this study is to find out the subjective reasons of motorists in traffic who commit traffic violations, such as violations of traffic signs, violations of traffic light, violations of vehicle completeness and violations of driver's equipment. The research method used is descriptive research with a qualitative approach. The research technique was carried out by studying literature, interviews, documentation, and observation. The results of the study, the reason for the driver to commit a violation is situational, the encouragement from an urgent situation and rushing in chasing time makes the driver do it. The second reason is individual, namely the encouragement from within oneself, such as a hobby of making modifications that are not up to standard. It would be nice for every motorist to obey the rules in traffic, not because of the guard from the police, especially the traffic police, but should have self-awareness.